Flat-of-the-curve medicine: A new perspective on the production of health - Johannes Schoder; Peter Zweifel (Health Economics Review, 2011)
Health economists have studied the determinants of the expected value of health status as a function of medical and non-medical inputs, often finding small marginal effects of the former. However, medical inputs may have an additional benefit in the form of a reduced variability of health status. Using the standard deviation of life expectancy in 24 OECD countries between 1960 and 2005, a 10 percent increase of health care expenditure is associated with a decrease of an estimated 0.42 percent. Willingness to pay for such a reduction of uncertainty may well exceed the extra health care expenditure in the United States and Switzerland. This implies that even in these two countries with very high health care expenditure per capita, flat-of-the-curve medicine need not be wasteful.
Keywords: 330; production of health; control over health status; willingness to pay